(untitled) (Bangladesh Journal of Agricultural Research, 2015)
In order to study the response of terminal heat stress on carbohydrate accumulation and grain yield of three wheat cultivars namely BARI Gom 25, BARI Gom 26 and Pavon 76 were sown on 18 November, 2011 in experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur in Bangladesh and two temperature regimes viz. normal (23°C in open field) and elevated (6 ± 1°C higher compare to open field mean air temperature in polythene chamber) were created. Elevated temperature shortened the grain filling duration by 5-day in BARI Gom 25 and BARI Gom 26 and 10-day in Pavon 76. Under elevated temperature condition grain starch synthesis was found to be stopped at 25 days after anthesis (DAA) in Pavon 76 which in BARI Gom 26 appeared 5-day later (30 DAA) in spite of higher level of soluble sugar in grain. Results indicate that early failure of conversion of sugar to starch rather than supply of soluble sugar under elevated temperature condition were responsible for shortening of grain filling duration and smaller grain size in all wheat cultivars. Smaller reduction of grain size and grain number along with smaller reduction of grain weight per main stem under elevated temperature condition finally contributed to sustain negligible loss of grain yield, biological yield and harvest index in BARI Gom 25 and BARI Gom 26 compare to Pavon 76. Bangladesh J. Agril. Res. 40(2): 205-215, June 2015